Open Innovation Strategies and Appropriability in Knowledge-Intensive Business Services: Evidences and Implications in the Brazilian Context - Eurico Sprakel; Andre Machado (BBR: Brazilian Business Review)
This paper analyzes open innovation strategies and their implications on appropriability and performance in Knowledge-Intensive Business Services (KIBS) firms which operate in the Brazilian market. This is cross-sectional research relying on the survey method. Data was collected through a questionnaire applied to 345 firms that provide Information Technology (IT) and Business Management Consulting services. Cluster analysis was the main technique employed for data analysis. The results showed that KIBS firms, whose inbound and outbound flows difference is small, eventually use appropriation mechanisms to a greater extent and adopt the selective revealing strategy more intensely. It is concluded that Brazilian KIBS firms adopt inbound knowledge flows more intensely, and that firms herein labelled as “neutral” presented greater appropriation and innovation performance than “externalizing”, “internalizing” or “very internalizing” firms.